USE OF COMMUNICATION MEDIA IN WETLAND FISHERIES DEVELOPMENT OF ASSAM - CHANDRA, GANESH (Journal of the Inland Fisheries Society of India, 2021)
The study was carried out in 21 districts of Assam. Two categories of respondents, namely fishers (106 nos) of floodplain wetlands and lower level field extension functionaries (30 officials) constituted the sample for the study. The study revealed that the interpersonal communication sources like consultation with Fisheries Extention Officer Beel manager and scientists were the most important sources for obtaining information on new, improved practices. Demonstration and consultation with progressive farmers were assigned second and third rank. Field extension functionaries preferred group discussion as the main source of extension programme followed by demonstration, fisheries publication and field day/ fish farmers’ day in the extent of use. The study has indicted that the interpersonal communication channels are important among the floodplain wetland fishers of Assam.Key words: Floodplain wetland, Assam, communication channels, extension functionaries